Beautiful and disgusting politics: Taming evil and the importance of controlling the uncontrollable - Yauri-Miranda, Jaseff Raziel (AusArt, 2019)
Evil doing is part of everyday social life and is extremely difficult to be counter-balanced by 'good' practices, let alone to be eliminated. Even in the realm of abstract politics, there is no simple solution or way to understand their overlapping nature. In that sense, this study explores the relationship between both sides through aesthetics and constructs a dialogical analysis transposed to politics. This relationship shows that beautiful and disgusting politics are not simply two sides of the same coin. The former has a limited potential to counterbalance the latter and, paradoxically, without its counter-part it has a limited potential to promote social transformations.